Investigating syntactic priming during sentence comprehension in developmental dyslexia: evidence for behavioral and neuronal effects - Kuerten, Anna Belavina (2017)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2017.